The role of selenium nanoparticles in reducing the effect of hydrogen peroxide on some hormones of female albino rats - Baydaa Talib Mahdi; Hanaa E. Mahood (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The study was conducted to evaluate the role of selenium and nanoselenium in reducing the effect of hydrogen peroxide on female hormones, and used 40 adult females and were randomly divided into four equal groups, the control group(C) , Water was given only Treatment group (T1): Hydrogen peroxide was given 1% with drinking water Treatment group (T2): Hydrogen peroxide was given 1% with drinking water and nanoselenium was dosed at a dose of 0.5mg/kg of body weight. Treatment group (T3): Hydrogen peroxide was given 1% with drinking water and regular selenium was dosed at a dose of 0.5mg/kg of body weight. the results of the current study showed that there was a significant increase in all the hormones studied in the two groups that dosed hydrogen peroxide with normal and nano selenium The best result was in the nanoselenium group.